Effect of Silica Fume on the Performance of Bacterial Concrete. Issue 1 (July 2021) - Doshi, Tejas; Patil, Umesh P; Patil, M B
Abstract: The main aim of this experiment is to study the effect of bacteria on the strength and durability properties of normal and silica fume (SF) concrete. The experiment is carried out to evaluate influence of Pseudomonas putida bacteria on the compressive strength, shear strength, sulphate attack and water sorptivity on concrete. Cement was replaced with 20% SF by weight. Three different cell concentrations (10 3, 10 5, 10 7 cells/ml) of bacteria were used in making the concrete mixes. The tests were carried out on the strength and durability properties after complete curing of 28 days. The inclusion of Pseudomonas putida in SF based concrete has an ability to enhance strength and improve durability of concrete. The study showed that concrete having bacterial infusion in all cell concentrations have increment in strength in comparison to reference mix. From the test results, it was concluded that, optimum cell concentration for concrete was found to be 10 5 cells/ml. The strength and durability properties were enhanced due to addition of bacteria in SF concrete compared to plain concrete. The calcite precipitation in concrete was visualized through SEM and is the reason for improvement in properties of concrete due to filling of pores by the growth of filler materials resulting in denser concrete.